2022
DOI: 10.1038/s41598-022-11294-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of blood pool and myocardial 3D printing in the diagnosis of types of congenital heart disease

Abstract: The study aimed to evaluate the effectiveness of blood pool and myocardial models made by stereolithography in the diagnosis of different types of congenital heart disease (CHD). Two modeling methods were applied in the diagnosis of 8 cases, and two control groups consisting of experts and students diagnosed the cases using echocardiography with computed tomography, blood pool models, and myocardial models. The importance, suitability, and simulation degree of different models were analyzed. The average diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…By improving the degree of verisimilitude of the visualization technique, the cognitive gap between the 2D medical images and the real heart in 3D can be closed, hence allowing the surgeons to decide the best surgical approach [ 25 ]. To date, there have been increasing reports on the usefulness of 3DPHM in redefining the best surgical strategies for complex CHD, in facilitating communication with patients, and in medical education for healthcare workers and students [ 1 , 2 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. With the advancement in high-quality holographic visualization, the application of MR in the medical field has also been explored in recent years for its use in pre-operative planning [ 19 , 20 , 21 , 22 , 23 , 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By improving the degree of verisimilitude of the visualization technique, the cognitive gap between the 2D medical images and the real heart in 3D can be closed, hence allowing the surgeons to decide the best surgical approach [ 25 ]. To date, there have been increasing reports on the usefulness of 3DPHM in redefining the best surgical strategies for complex CHD, in facilitating communication with patients, and in medical education for healthcare workers and students [ 1 , 2 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. With the advancement in high-quality holographic visualization, the application of MR in the medical field has also been explored in recent years for its use in pre-operative planning [ 19 , 20 , 21 , 22 , 23 , 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Congenital heart disease (CHD) is considered one of the most challenging pathologies to manage in clinical practice due to its broad spectrum of morphologies that vary from individual to individual [ 1 , 2 , 3 ]. If surgery or intervention is required to repair the heart lesion, a full understanding of the anomalous cardiac structure plays a fundamental role in a successful surgery [ 3 , 4 ]. However, current visualization techniques based on cardiac computed tomography (CT) or magnetic resonance imaging with volume rendering lack realism as they do not depict the actual depth of the object [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mimics Innovation Suite 19.0 (Materialise HQ, Leuven, Belgium) was used for processing. The blood pool modelling method was used for the reconstruction of the whole heart 11 . Zbrush 4R9 (Pixologic, Los Angeles, U.S.A) was used to smooth the model surface and reconstruct predictive surgical models.…”
Section: Methodsmentioning
confidence: 99%
“…3D printed models are increasingly used in medical education, with promising results achieved when compared to traditional teaching methods. Studies have shown its educational value in two areas as assessed by medical students and clinicians (cardiothoracic surgeons, cardiologists, cardiac imaging specialists including radiologists and radiographers, residents or registrars, and clinical nurses) [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. Table 1 summarizes studies reporting the medical education of 3D printed models compared to traditional teaching methods or other advanced tools.…”
Section: Education Value Of 3d Printed Models In Cardiovascular Diseasementioning
confidence: 99%
“…There is consistent agreement among these studies that 3D printed models significantly increased the participants’ knowledge of cardiac anatomy and CHD pathology when compared to conventional education or imaging approaches. Significantly higher scores were achieved in the 3D printing groups than those in the control groups, and this is especially apparent when complex CHD was involved [ 36 , 39 ], and 3D printed models were rated as an excellent tool for anatomy teaching, as well as improving diagnostic rate assessed by both experts and students [ 39 ].…”
Section: Education Value Of 3d Printed Models In Cardiovascular Diseasementioning
confidence: 99%